The Archaeology of Human-Environmental Dynamics on the North American Atlantic Coast - Thompson, Victor D.; Rick, Torben C.; Turck, John A.; Reeder-Myers, Leslie A. (Book collections on Project MUSE., 2019)
« This edited volume brings together leading scholars focused on the Native American peoples who called the Atlantic coast home for thousands of years. Each chapter will address an individual region of the Atlantic coast of North America, ranging from the Canadian Maritime Provinces to the Florida Keys. »--